2013
DOI: 10.1002/jmv.23661
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and epidemiological features of hepatitis C virus infection in South Korea: A prospective, multicenter cohort study

Abstract: The epidemiological and clinical features of hepatitis C virus (HCV) infection in South Korea were examined in a prospective, multicenter cohort study that included 1,173 adult patients with positive results for anti-HCV antibody who completed a questionnaire survey on the risk factors for HCV infection from January 2007 to December 2011 at five university hospitals. The HCV cohort had a mean age of 55.4 years with 48.3% men, and diagnostic categories of acute hepatitis (n = 63, 5.3%), past infection (n = 37, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 32 publications
1
74
2
Order By: Relevance
“…These higher SVR rates in Korean patients seem to be partly explained by a higher proportion of favorable IL-28B polymorphisms [17]. Also, the demographic patterns, including risk factors and genotype distribution, of the Korean HCV patients were different from those of other countries [18]. The natural history and risk factors for disease progression of chronic HCV infection have primarily been studied in Western countries or Japan, and there is little information on Korean patients [5,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…These higher SVR rates in Korean patients seem to be partly explained by a higher proportion of favorable IL-28B polymorphisms [17]. Also, the demographic patterns, including risk factors and genotype distribution, of the Korean HCV patients were different from those of other countries [18]. The natural history and risk factors for disease progression of chronic HCV infection have primarily been studied in Western countries or Japan, and there is little information on Korean patients [5,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…From a public health perspective, efforts are currently focused toward the implementation of treatment strategies that may decrease rates of onward transmission [5]. Globally, there has been considerable interest in assessing the cost-effectiveness of screening programs for HCV; analyses have been performed in several countries with a high prevalence of HCV including the US, Japan and Egypt [612].…”
Section: Introductionmentioning
confidence: 99%
“…[19] Using those cohort data, this study aimed to elucidate the incidence of liver cirrhosis, HCC, and all-cause mortality in chronic hepatitis C patients, and to identify the risk factors related to those clinical outcomes. To the best of our knowledge, this is the first prospective cohort study in a real-world clinical practice that observed the major outcomes of chronic hepatitis C patients in an HBV-prevalent Asian region.…”
Section: Introductionmentioning
confidence: 99%